Wawasan Perilaku Hidup Bersih dan Sehat (PHBS) di Masa Kenormalan Baru dalam Upaya Mencegah Penyebaran Covid-19 di Lingkungan Sekolah - Rizal Koen Asharo; Achmad Arifiyanto; Firas Khaleyla; Choirina Tamimi Rahmadi (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The Indonesian government has long supported educational institutions to provide clean and healthy living habits through the Ministry of Health. However, clean and healthy living habits in schools seem to be increasingly important nowadays, because in the new normal era of the corona virus pandemic, children will soon return to school. Schools must maintain a clean and healthy lifestyle by involving teachers, students, and the community in the school environment and following certain health-related procedures. The school environment also needs to be made clean and healthy. The benefit of maintaining a clean and healthy lifestyle at school is to create a clean and healthy environment. In this way, the teaching process will run smoothly, and the health of teachers, students and the surrounding community will not be disturbed. Education on clean and healthy living habits is packaged in a national seminar in collaboration with SMA Negeri 19 Surabaya on Sunday, March 28, 2021. This activity is carried out in the form of lectures with the help of power points, through a zoom meeting platform which is also broadcast live on Youtube. The material presented includes three things with the author himself as the resource person and moderator of the event. The three materials are about Covid-19 and its development, the Covid-19 vaccine and its effectiveness, and the application of clean and healthy living habits in an effort to fight Covid-19. As for the participants, students from SD, SMP, and SMA with a total of 78 people and general participants reaching 11 people. This service is carried out independently and is carried out well in accordance with the objectives expected by the executor.